Inovasi Dalam Online Marketing Dan Pengaruhnya Terhadap Kualitas Pelayanan, Kepercayaan, Loyalitas, Dan Word Of Mouth Pada Konsumen - Handy Januar Permana; Wahyu Hidayat; Arif Marjuki (UNIVERSITAS RAHARJA, 2017)
The background of this paper discusses the role of consumer perceptions of innovation a website as a factor influencing their evaluation of service quality, development of trust, loyalty and word of mouth behavior on the site. This study aims to answer the question the extent not experienced site service innovation evaluation of the influence of website quality, trust, loyalty and word of mouth. Therefore, to answer this question this study developed and tested a theoretical model that seeks to explain the perceived effects of site-service innovation on perceived e-service quality, trust, loyalty sites and word-of-mouth behavior in e-retail market space. The study design is based on valid responses werecollected from a questionnaire survey of 120 people located in Jakarta. The variables examined in this study using the Partial Least Squares (PLS), specifically PLS-IMAGE v.3.00 to assess the relevance of the predictions of the conceptual model, and test the hypothesis relationship as depicted in picture. Results showed that when an e-retail sites considered positive for providing an innovative experience more positive evaluations affect the overall perception of the quality of online services, high level of trust and loyalty websites and the positive side of the conversation behavior mouth. This study provides important implications for the delivery of online services and online branding, especially foronline retailers. Additional research is needed to see the impact of an innovation in online marketing by adding other variables that are considered important are associated with innovation.